Adaptive control of light attenuation for optimizing microalgae production. (June 2015) - Mairet, Francis; Muñoz-Tamayo, Rafael; Bernard, Olivier
Abstract : Highlights: We propose two nonlinear controllers for light-limited microalgae culture. The global asymptotic stability of the closed-loop system has been demonstrated. We show the robustness of the control law with respect to noise measurements. Such controller is of particular interest for optimizing biomass production. Abstract: The light attenuation factor, defined by the ratio between the incident light and the light at the bottom of the reactor, is a key operating parameter for light-limited phototrophic culture. Here, two nonlinear control laws have been proposed in order to regulate this ratio: a static controller, which is input-to-state stable with respect to measurement noise, and an adaptive controller. Then, we propose a set-point for the light attenuation factor in order to optimize microalgae productivity under constant illumination. Finally, numerical simulations illustrate how the adaptive controller can be used to optimize biomass productivity under realistic day–night cycles.